The effect of coordination exercises with neuromuscular facilitation (PNF) for the treatment of frozen shoulder injury - Abbas, Kawther; Jameel, Israa (Journal of Physical Education, 2023)
The study aimed to prepare neuromuscular compatibility (PNF) exercises to treat frozen shoulder injury and to identify the effect of using (PNF) exercises on the range of motion of the shoulder joint. The experimental method was used to suit the research problem, and the research sample was chosen intentionally and numbered (8).  were injured. As for the field research procedures, the two researchers conducted preliminary range of motion tests, which are (flexion test, extension test, abduction test, horizontal abduction test, horizontal adduction test, inward rotation test, and outward rotation test), and then conducted the main experiment for two months at a rate of three units per week, with a total of ( 8) weeks, with a total of (24) treatment sessions. The session time ranged in the treatment units (20-30 minutes), in which PNF exercises were used with an intensity determined according to the severity of the pain. After that, post-tests were conducted, taking into account the conditions that took place in the pre-tests. As for the results of the research Significant differences appeared between the pre- and post-tests in the range of motion tests used in the research. The researchers also concluded the effectiveness of using neuromuscular compatibility exercises (PNF) to treat frozen shoulder injury and also increase the range of motion of the shoulder joint in the research sample. The researchers recommended developing neuromuscular compatibility exercises (PNF). ) within the rehabilitation programs of treatment centers, as well as adopting these exercises to rehabilitate shoulder injuries.